The Jurisprudence of Noise: An Islamic Legal Analysis of the “Sound Horeg” Phenomenon in Indonesia - Ahmad Nabilul Maram; A’azliansyah Farizil Anam; Ramatoulaye Senghore (Dialogia, 2025)
The phenomenon of sound horeg as a form of excessive and competitive contemporary cultural expression has raised theological, social, and ethical issues that urgently need to be studied scientifically. This practice is not merely entertainment, but has shifted to become a symbol of luxury and public arrogance that has social, medical, and moral implications. This research is important because there has been no comprehensive legal-theological study that systematically assesses this phenomenon from an Islamic legal perspective. Using a qualitative and interpretive theological-legal approach, this study combines the taḥqīq al-manāṭ method (empirical investigation of factual reality) with Mustafa Muslim's inductive thematic interpretation, which interprets verses of the Qur'an through keyword analysis and the context of revelation. The synthesis of the interpretation results is then integrated with the principles of uṣūl al-fiqh and maqāṣid al-sharī‘ah, especially lā ḍarara wa lā ḍirār, to produce a contextually relevant legal analysis. The results of the study show that sound horeg, in its current form, fundamentally contradicts the principles of Islamic ethics and law because it contains elements of wastefulness (isrāf and tabdzīr), public harm (ḍarar), immoral entertainment (lahw al-ḥadīth), and social arrogance (kibr). These findings confirm that Islamic jurisprudence has adequate methodological tools to navigate modern phenomena without losing its normative values, while opening opportunities for the development of a constructive cultural ethical model that is in line with the objectives of Sharia. REFERENCES 'Asyur, Muhammad Thohir bin. "Tahrir Wa Al-Tanwir." In Vol. 15. Tunisia: Dar al-Tunis li al-Nasyr, 1984. ———. "Tahrir Wa Al-Tanwir." In Vol. 8. Tunisia: Dar al-Tunis li al-Nasyr, 1984. Abbas, H, and M Sajjad. “English-6 The Concept of Tortious Liability under Islamic Law: An Inquiry into the Question of Compensatory Damages.” Al-Aijaz Research Journal of Islamic Studies & Humanities, 2021. https://doi.org/10.53575/english6.v5.02(21).68-80. Abels, Birgit. “Austronesian Soundscapes: Performing Arts in Oceania and Southeast Asia,” 2010. https://doi.org/10.5117/9789089640857. Abu Bakar, Azreen Zuhairi, Walid Nabghan, Moslem Elhaei, Zakiah Abul Khassim, Wan Azani Mustafa, and Noor Hazirah Abd Aziz. “Comprehensive Review on Islamic Ethics and the Rise of Technology.” Journal of Advanced Research in Applied Sciences and Engineering Technology 51, no. 1 (September 4, 2024): 184–94. https://doi.org/10.37934/araset.51.1.184194. Adrian, Gede Arga. “Beware of Sound Horeg Damaging Hearing.” UMS Newsletter, 2024. https://www.ums.ac.id/berita/teropong-jagat/waspada-sound-horeg-merusak-pendengaran. Agastya, Fajar. “Sound Horeg Entrepreneurs Say MUI Fatwa Hinders Indonesia from Becoming a Developed Country.” Metro TV News, 2025. Al-Qurtubi, Abu ’Abdillah Muhammad. “Al-Jami’ Al-Ahkam Al-Qur’an.” In Vol. 9. Beirut: Al-Resalah Publisher, 2006. Al-Suyuti, Jalaluddin. Asybah Wa Al-Nadzair. Beirut: Dar Al-Kutub Ilmiyah, 1983. Al-Syaukani, Muhammad bin 'Ali. "Irsyad Al-Fuhul Ila Tahqiq Al-Haq Min Ilmi Al-Usul." In Vol. 2. Beirut: Dar al-Kutub al-'Arabi, 1999. Al-Tabari, Ibn Jarir. "Jami' Al-Bayan 'an Ta'wil Al-Qur'an." In Vol. 14. Cairo: Hajr li al-Ṭabā'ah wa al-Nashr wa al-Tauzī' wa al-I'lān, 2001. Al-Zuhaili, Wahbah. “Tafsir Al-Munir Fi Al-’Aqidah Wa Al-Syariah Wa Al-Manhaj.” In Vol. 8. Damascus: Dar al-Fikr, 2009. Aprilian, Elham Wulan, Arif, and Sari Dewi Poerwanti. “The Impact of SoundHoregterhadap Parade on the Socioeconomic Conditions of the Bumirejo Village Community, Blitar Regency.” Jurnal Intervensi Sosial 4, no. 1 (2025): 13–20. https://doi.org/https://doi.org/10.32734/intervensisosial.v4i1.20197. Arafah, I. “The Sadd Adz-Dzari’ah Approach in Islamic Studies” 5 (2020): 68–86. https://doi.org/10.32505/muamalat.v5i1.1443. Arifin, Misbahul, and Umar Mansur. “Analysis of Fiqh on The ‘Soundhoreg’ Trend: A Study of Ethics and Limits of Audio Use.” LexIslamica: A Multidisciplinary Approach to Islamic Law and Its Contemporary Applications 1, no. 1 (2025): 1–11. https://doi.org/10.33650/joki.v4i2 Arum, Hafidza Sanshia, and Mawardi Mawardi. “Waste and Overconsumption in Modern Finance: An Analysis of Qs Values. Al-Isra: 26-27.” Al-Muzdahir : Journal of Sharia Economics 7, no. 1 (January 1, 2025): 26–27. https://doi.org/10.55352/ekis.v7i1.1375 Arzroomchilar, Ehsan, and Maryam Olamaiekopaie. “Where Technology Meets Islam: Towards an Islamic Perspective on Technology.” Journal of Islamic Thought and Civilization 12, no. 2 (November 11, 2022): 14–27. https://doi.org/10.32350/jitc.122.02. Bram, Damianus. “Sound Horeg: East Java’s Unique Entertainment That Has Taken Social Media by Storm, Pros and Cons Emerge.” solobalapan.com, 2025. https://solobalapan.jawapos.com/berita-utama/2306351459/sound-horeg-hiburan-khas-jawa-timur-yang-menggetarkan-media-sosial-pro-dan-kontra-pun-bermunculan. Caillouët, Jean-David. “The Voices of South-East Asian Soundscapes.” Creative Research in Music, 2020. https://doi.org/10.4324/9780429278426-11. Dahlan, Moh, Mohammad Reevany Bustami, Makmur, and Siti Mas’ulah. “The Islamic Principle of Ḥifẓ Al-Nafs (Protection of Life) and COVID-19 in Indonesia: A Case Study of Nurul Iman Mosque of Bengkulu City.” Heliyon 7, no. 7 (July 2021): e07541. https://doi.org/10.1016/j.heliyon.2021.e07541. Darmawan, Mohammad Dzikri, and Riska Efendi. “The Role of Horeg Sound in Cultural and Economic Transformations of Mengare Island.” Turath: Interdisciplinary Journal of Economics 1, no. 1 (2024): 1–13. https://doi.org/https://doi.org/10.15642/turath.2024.1.1.1-13. Faiz, Abd. Aziz, Muthi’ah Zuhrotunnisa, Subkhani Kusuma Dewi, and Zulfan Nabrisah. “Middle-Class Muslims Piety Festival in Indonesia Islamic Contemporary.” IBDA` : Journal of Islamic and Cultural Studies 21, no. 2 (September 14, 2023): 169–86. https://doi.org/10.24090/ibda.v21i2.6859 Fakher, Ali. “Contemporary Issues in the Provisions of Neighborhood.” Journal of Umm Al-Qura University for Sharia’h Sciences and Islamic Studies, no. 95 (December 19, 2023): 143–55. https://doi.org/10.54940/si26141842. Fauzi, Ahmad, Nasrulloh, and Annafik Fuad Hilmi. “The Influence of Sound Horeg on the Surrounding Environment in the Perspective of Al-Qur’an Surah Al-A’raf Verse 31 in Ibn Kathir’s Interpretation.” Journal of International Multidisciplinary Research 2, no. 11 (2024): 170–76. https://doi.org/https://doi.org/10.62504/jimr973 Fikri, Mohammad. “When Sound is Forbidden: Sound Horeg and Noise Politics in Jember.” Multikultural: Journal of Social Sciences 3, no. 2 (2025): 1–17. https://doi.org/10.20527/multikultural.v3i2.673. Fikria, Mohammad, Didik Suharijadib, and Hasan Baharun. “Sound Horeg as Popular Cultural Discourse: A Cultural Critical Study of Religious Responses in East Java.” Tutur Sintaksis: Journal of Indonesian Language and Literature Education, Linguistic Studies and Local Wisdom 1, no. 1 (2025): 25–41. https://doi.org/https://doi.org/10.64344/trst.v1i1.31 Firdaus, Syarif, and Mukhsin Achmad. “An Epistemological Study of Islamic Law in the Context of the Indonesian Ulema Council’s Fatwa.” JURNAL PUSAKA 14, no. 1 (June 18, 2024): 42–55. https://doi.org/10.35897/ps.v14i1.1451 Fitra, Akhmad Aidil, and Yousuf Aboujanah. “Gadamerian Hermeneutical Analysis of Hasbi Ash-Shiddieqy’s Interpretation of QS. Luqman (31):6 in the Context of Contemporary Entertainment Discourse.” Al-Karim: International Journal of Quranic and Islamic Studies 3, no. 1 (March 30, 2025): 59–78. https://doi.org/10.33367/al-karim.v3i1.6839 Fitria, Auliana Salsabila. “Legal Supervision of Renters Using Sound Gigantic That Exceeds The Deibel Limit From The Perspective of Positive Law and Maqashid Syariah (Study at the Civil Service Police Unit of Malang Regency).” Thesis: UIN Maulana Malik Ibrahim Malang, 2025. Ghani, Zulkiple Abd, and Suria Hani A. Rahman. “Transforming Islamic Entertainment and Values in Malaysian Films.” Journal of Arab & Muslim Media Research 16, no. 1 (April 1, 2023): 3–16. https://doi.org/10.1386/jammr_00053_1. Hakiki, Imron, and Aloysius Gonsaga AE. “Malang Regency Government Prepares Derivative Regulations Related to Sound Horeg.” Kompas, 2025. http://surabaya.kompas.com/read/2025/08/18/132951778/pemkab-malang-siapkan-aturan-turunan-terkait-sound-horeg. Haq, Sansan Ziaul. “Questioning the Validity of Sadd Al-Dharai‘ as a Basis for Islamic Law: The Epistemological Polemic of Ushuliyyin.” AL-AQWAL : Journal of Islamic Law Studies, 2024. https://doi.org/10.53491/alaqwal.v3i02.1035. Haris, Arkin, Aris Widodo, Irma Dwi Tantri, and Siti Sarah. “Eco-Maqāṣid in Climate Change Campaigns: From an Ecolinguistics Study to the Philosophy of Islamic Law.” Al-Manahij: Journal of Islamic Law Studies, August 13, 2024, 219–36. https://doi.org/10.24090/mnh.v18i2.10652. Hassan, Wan Zulkifli Wan, and Laizatulnorhasikin Mohd Adom. “Theory and Application of Sadd Al-Dhara’i‘ (Blocking the Means) in Curbing Crime in Malaysia.” International Journal of Academic Research in Business and Social Sciences 12, no. 4 (April 5, 2022). https://doi.org/10.6007/IJARBSS/v12-i4/13084. Huda, Miftahul, and Bilal Ramadhan. “Husband of Victim Who Died at Sound Horeg Carnival: His Voice Was Loud, It Doesn’t Make Sense to Say It Wasn’t Dangerous.” Kompas, 2025. https://surabaya.kompas.com/read/2025/08/04/134617578/suami-korban-meninggal-di-karnaval-sound-horeg-suaranya-keras-nggak-masuk Irawan Rangkuti, Chairil, Sukiati Sukiati, and Ramadhan Syahmedi Siregar. “The Concept of Maqashid Sharia in the Effectiveness of the Implementation of Presidential Regulation No. 72 of 2021 Concerning the Handling of Stunting in Mandailing Natal Regency.” Journal of Law, Politics, and Humanities 4, no. 5 (July 10, 2024): 1404–17. https://doi.org/10.38035/jlph.v4i5.526. Kamal, Mohammad Arif, Tahsinur Rahman Warsi, and Osama Nasir. “ISLAMIC PRINCIPLES AS A DESIGN FRAMEWORK FOR URBAN SYSTEM: ENVIRONMENTAL CONCERN AND SUSTAINABLE DEVELOPMENT.” Journal of Islamic Architecture 7, no. 4 (December 30, 2023): 699–712. https://doi.org/10.18860/jia.v7i4.21187. Kapanlagidotcom. The Sound Horeg Phenomenon, Broken Glass Brings Joy - Tarig Invites Up to 1 Truck Worth 1 Billion. Indonesia, 2025. https://youtu.be/vZs2Mmtw8bY?si=34mbNOnwmCN3a7Si. Kathīr, Ibn. “Tafsīr Al-Qur’ān Al-’Aẓīm.” In Vol. 3. Cairo: Maktabah al-Islamiya, 2005. Katsir, Ibn. “Tafsir Al-Qur’an Al-’Adzim.” In Vol. 5. Cairo: Maktabah al-Islamiyyah, 2003. Kh, Allya Salsa Bilatul, Diajeng Anugrah Cantika Sari, and Fatkurohman Nur Rangga. “The Development of Sound Systems as Culture and Social Competition in Sumbersewu Village, Muncar District, Banyuwangi.” RISOMA: Journal of Social Humanities and Education Research 2, no. 4 (2024): 220–44. https://doi.org/https://doi.org/10.62383/risoma.v2i4.156 Khaleel, Fawad, and Alija Avdukic. “Islamic Classical Literature (A.D. 950–1450) on Institutionalization of Ethics for Regulating Markets and Society.” Religions 15, no. 12 (December 9, 2024): 1496. https://doi.org/10.3390/rel15121496 Khalil, Atif. “Humility in Islamic Contemplative Ethics.” Journal of Islamic Ethics 4, no. 1–2 (December 15, 2020): 223–52. https://doi.org/10.1163/24685542-12340048. Kasim, Muh. Isra Syarif, and Ashal Mattanra. “The Application of the Principle of Lā Ḍarara Wa Lā Ḍirār in the Use of Firecrackers to Repel Plant Pests.” AL-QIBLAH: Journal of Islamic Studies and Arabic Language 3, no. 5 (September 27, 2024): 843–65. https://doi.org/10.36701/qiblah.v3i5.1746 Mohamad Yunus, Mohamad Ismail Bin. “The Position and Application of Islamic Legal Maxims (Qawaaid Al-Fiqhiyyah) in the Law of Evidence (Turuq Al-Hukmiyyah).” FIAT JUSTISIA: Journal of Law 13, no. 1 (April 2, 2019): 43. https://doi.org/10.25041/fiatjustisia.v13no1.1479 Muhamad Shadiq, Gusti, Jalaluddin Jalaluddin, Fathurrahman Azhari, and Fahmi Hamdi. “A Study of Istinbath Methodology and Islamic Legal Patterns in Fatwa Institutions in Indonesia (LBMNU, Muhammadiyah Tarjih Council, and MUI Fatwa Commission).” Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory 2, no. 2 (June 8, 2024): 684–99. https://doi.org/10.62976/ijijel.v2i2.546 Muslim, Mustafa. Mabahis Fi Al-Tafsir Al-Maudu’i. Damascus: Dar al-Qalam, 2000. Ourkia, Abderrazak, and Mohamad Abdullah Alsaied. “The Impact of Islamic Jurisprudence Principles on the Urban Planning of Historic Cities.” Journal of Posthumanism 5, no. 5 (April 29, 2025). https://doi.org/10.63332/joph.v5i5.1304. Pakeeza, Fariha Fatima Dr Shahzadi. “Application of Five Fundamental Islamic Legal Maxims (Al-Qawa’id Al-Fiqhiyyah Al-Khams Al-Kubra) to Islamic Criminal Law” 13 (2020): 1–13. https://doi.org/10.51506/JIHAT-UL-ISLAM.V13I2.149 Rashid, Dr. Burhan. “Humility and Arrogance: Their Respective Legal and Ethical Positions in Islam.” The Journal of Contemporary Issues in Business and Government 27 (2021): 372–81. https://doi.org/10.47750/CIBG.2021.27.03.051. Rinanda, Hilda Meilisa. “Facts About a Young Mother Who Died While Watching Sound Horeg in Lumajang.” detikjatim, 2025. https://www.detik.com/jatim/berita/d-8045597/fakta-fakta-ibu-muda-meninggal-saat-nonton-sound-horeg-di-lumajang. Sanabila Khairil Ahya, and Tajul Arifin. “Neighbor Disputes in the Perspective of Muttafaq ‘Alaih Hadith and Article 503 of the Criminal Code.” JISPENDIORA Journal of Social Sciences, Education, and Humanities 3, no. 2 (June 19, 2024): 100–110. https://doi.org/10.56910/jispendiora.v3i2.1493. Silaban, Yunita Enzelina, Akhmadi Surya Nata, Uci Purnama Purba, and Reni Agustiani. “Analysis of Noise Levels at Children’s Playground X in Palangka Raya City.” Indonesian Physics Research Journal 4, no. 2 (June 30, 2024): 42–54. https://doi.org/10.33019/jrfi.v4i2.5272. Thahir, A. Halil. “Towards the Multidimensional Ushul Al-Fiqh: A Study of the Integration of Science in the Fatwa of Majelis Ulama Indonesia.” Samarah: Journal of Family Law and Islamic Law 8, no. 2 (May 7, 2024): 687. https://doi.org/10.22373/sjhk.v8i2.19686. MUI Digital Editorial Team. “MUI East Java Fatwa Commission Invites Doctors and Sound Horeg Businesspeople to Discuss Fatwa.” MUI Digital, 2025. https://mui.or.id/baca/berita/komisi-fatwa-mui-jatim-undang-dokter-hingga-pebisnis-sound-horeg-bahas-fatwa Wahid, Sahid, Achmad Musyahid, and Rahmatiah HL. “The Logic of Impairment in Islamic Law: Philosophical Perspective as a Foundation for Ethics Education.” Journal of Education Review Provision 4, no. 3 (December 23, 2024): 25–28. https://doi.org/10.55885/jerp.v4i3.462. Yilmaz, Ekrem. “An Overview of Waste in the Context of Islamic Economics and Heterodox Approaches: On Common Discourses.” International Journal of Ethics and Systems, April 16, 2024. https://doi.org/10.1108/IJOES-08-2023-0177. Zakariyah, Luqman. Legal Maxims in Islamic Criminal Law: Theory and Applications. Leiden: Brill | Nijhoff, 2015. https://doi.org/10.1163/9789004304871. Zuhdi, Syaifuddin, and Rizki Widyawati. “The Islamic Legal Maxims in Consideration of Religious Court Judge.” In Advances in Social Science, Education and Humanities Research, 280–86. Atlantis Press, 2022. https://doi.org/10.2991/assehr.k.220501.032.